Strength and conditioning coaches' perceptions of sport psychology strategies - Quartiroli, A.; Moore, E. W. G.; Zakrajsek, R. A. (The Journal of Strength and Conditioning Research, 2022)
Strength and conditioning coaches (SfCCs) hold a central role in the development of student-athletes. Although they certainly focus on student-athletes' physical skill development, SCCs are in an ideal position to integrate mental skills into their strength and conditioning sessions. For example, sport psychology (SP) strategies can be used within strength and conditioning sessions to assist in athlete exercise execution by regulating arousal, improving concentration, confidence, as well as improve self-correction through self-talk and imagery. The purpose of this study was to assess collegiate SCCs' use of SP skills/strategies. A total sample of 415 SCCs (19.7% return rate) across the United States participated in an online survey. Although the majority of these coaches reported having less than moderate training in SP (59.9%), they also reported a moderate to high use of certain SP strategies (e.g., goal setting, self-talk). Strength and conditioning coaches' familiarity with, knowledge of, and confidence to use the SP strategies were found to be predictors of SCCs' frequency of SP strategy use. This study aimed to provide an initial exploration of SCCs' understanding and use of specific SP strategies, which was influenced by the SCCs' perceived level of preparation to use these strategies. For SCCs to be able to purposefully and confidently incorporate SP strategies into training sessions, the current study suggests the need for specific training aimed to enhance the SCCs' knowledge of and confidence in using specific SP strategies.